Framework of Critical Success Factors for Lean Implementation in Vietnam Manufacturing Enterprises - Minh, Nguyễn Đạt; Nguyên, Nguyễn Danh; Tuấn, Lê Anh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 31 No 5E, 2015)
Abstract: Lean manufacturing is a popular approach for organizations to improve productivity [1]. Lean manufacturing focuses on the systematic elimination of wastes and non-value added activities in production. Lean manufacturing was originally introduced by Toyota Motors in the 1950s as a secret weapon to secure advantage over competitors. Although many enterprises succeed in applying lean manufacturing around the world, less than 20 per cent of them have achieved and maintained lean activities for an extended time. This research presents critical factors for constituting the successful implementation of lean manufacturing inVietnam enterprises. Six dimensions in a lean manufacturing transformation model are presented in the research, specifically: (1) Strategic initiatives, (2) Process management, (3) Change management, (4) Human resource management, (5) Situation management, and (6) External management. Keywords: Lean manufacturing, critical success factors, manufacturing enterprises.